FITUR-FITUR SUPRASEGMENTAL DALAM BAIT PEMAWAK KIDUNG TANTRI NANDAKAHARANA - I Gusti A. Intan Purnama, D.T. (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2013)
This studi analyse couplet of Pemawak Kidung Tantri Nandakaharana. Focus of this stucy is basic subsegmental features and the variations. This study based on theory of subsegmental features (rhythm, accent, and intonation). This aim of study arranges the basic form of Pemawak couplet in Kidung Tantri Nandakaharana. This couplet has eigth lines. Each lines have diferent rhythm, accent, ant intonation. First line and third line were dominated by flat intonations, whereas the domination of flat intonation increase in second line, fouth line until eighth line. It was happened caused by there are heavy voice and changes of rhythm in each silabels. Beside finded the basic form, there are variations that based on the basic form. The variations caused by affected of interpretation and perception of singer.